TERMS OF SALE BY INSTALLMENTS - Suliman, Khalaf Ibrahim (Journal of Duhok University, 2018)
We dealt under the terms of the sale of installments, which is one of the important topics in positive law and Islamic jurisprudence, which raises many problems and differences of jurisprudence and legal. And the absence of studies in the books of Islamic jurisprudence, and the entry of banks to finance this type of transactions and interrelationships between the emerging relationships between the founding companies for installment projects and the public of people, and observed the spread of sales by simplification in many transactions of individuals and nations. In order to deal with this subject, we have divided it into two sections. The first concerns the terms of sale in installments agreed upon between non-Islamic jurisprudence and positive law. The second relates to the conditions of sale by installments, which are mentioned only in positive law. At the end of the research, we reached the most important results, namely, that selling by installments is a sale of credit according to which the price is paid on periodic installments that are paid for each or every part after the selling is delivered, and the price involved in selling by installments on an increases in the cash for term price . That the increase does not fall under the section of usury prohibited in Islamic law, either the recommendations we pointed to the need to work to codify and apply the provisions of Islamic legislation, and the cancellation of any increase approved by law or agreement or custom on the debt of the price or installments or loan financing the sale of installments under any name of interest or A Bank or administrative expenses other than wages or service commission, compensation and satisfaction of the debtor without condition. And the enactment of special rationing by installments following the rapid modern development in this system and includes the sale of real estate and services in various areas by installments